Magnetic particles for multidimensional in vitro bioanalysis. Issue 5 (23rd June 2021) - Lin, Gungun
Abstract: Multidimensional or multiplex bioanalysis represents a crucial approach to improve diagnostic precision, increase assay throughput and advance fundamental discoveries in analytical industry, life science, and nanomedicine. Along this line, bio‐interfacing magnetic particles have been playing an important role. Fully exploiting the properties of magnetic particles is the key to tailoring recent technology development for better translational outcomes. In this mini‐review, typical magneto‐physical dimensions of magnetic particles are introduced. Recent progress of implementing these dimensions with advanced sensor and actuator technologies in multiplex bioanalysis is discussed. Outlooks on potential biomedical applications and challenges are provided. Abstract : In article number 20200076, Gungun Lin has summarized typical magneto‐physical dimensions of magnetic particles and discussed recent progress of implementing these dimensions with advanced sensor and actuator technologies for multiplex bioanalysis. The review also identified the challenges and highlighted a few emerging directions of applying magnetic particles for multidimensional and multiscale bioanalysis.